Developing the Spirit of Entrepreneurship through Training in Making Sprinkle Chili Powder (Bon Cabe) - Ni Made Ayu Gemuh Rasa Astiti; Anak Agung Made Semaryani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Entrepreneurship is a constantly changing field, and people are always looking for chances to start businesses that will not only help them reach their own goals but also grow their communities' economies. One way is to make Sprinkle Chili Powder, which is also known as Bon Cabe. Many people love this versatile and well-known condiment, which makes it a great business chance for people who want to start their own business. To use this potential, a full training program has been created to encourage people to be entrepreneurial and teach them how to make high-quality Bon Cabe. Consumers will tend to choose products with attractive packaging, compared to products whose packaging is plain or simple and unattractive. There are quite a lot of chilli products produced in the Sidekarya Farmer Group. The process of processing chilli products into chilli bonds produced by partners is very constrained, especially in product processing, packaging and marketing according to prices. The main problem that will be the focus of solving the problem is how to make processed chillies into BonCabe (Sprinkle Chili Powder) and improve the product packaging so that it can attract consumers to buy products, Participants who want to get into the lucrative business of Bon Cabe making can use this training program as a stepping stone. Participants will not only learn the skills they need to be great entrepreneurs, but they will also help the local economy grow and become more diverse by combining classroom learning with hands-on experience. The program shows how real training can change the lives of people who want to become entrepreneurs and help them reach their full potential. It's not just about producing a well-liked condiment; it's also a life-changing event that enables people to turn their dreams into successful businesses.